2007
DOI: 10.2220/biomedres.28.43
|View full text |Cite
|
Sign up to set email alerts
|

The anti-fibrotic effect of green tea with a high catechin content in the galactosamine-injured rat liver

Abstract: Previously, we reported that the oral administration of green tea rich in catechins restored levels of several biomarkers increasing in galactosamine-treated rats to nearly control values. These biomarkers included serum transaminase activities, serum concentrations of tumor necrosis factor-α and interleukin 1-β, and the hepatic mRNA expression of these inflammatory cytokines. In the present study, we examined possible anti-fibrotic effects of green tea in galactosamine-induced hepatitis. The results of the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 22 publications
3
8
0
Order By: Relevance
“…This study found a significant increase in hepatic gene expression of TGF‐β1 and collagen type I 48 hr post GalN administration, compared to controls. Similar findings were previously reported (Abe et al, ; Czaja et al, ; Jonker, Dijkhuis, Boes, Hardonk, & Grond, ). TGF‐β1 is a profibrogenic cytokine that plays a major role in the development of hepatic fibrosis (Abe et al, ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study found a significant increase in hepatic gene expression of TGF‐β1 and collagen type I 48 hr post GalN administration, compared to controls. Similar findings were previously reported (Abe et al, ; Czaja et al, ; Jonker, Dijkhuis, Boes, Hardonk, & Grond, ). TGF‐β1 is a profibrogenic cytokine that plays a major role in the development of hepatic fibrosis (Abe et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…Similar findings were previously reported (Abe et al, ; Czaja et al, ; Jonker, Dijkhuis, Boes, Hardonk, & Grond, ). TGF‐β1 is a profibrogenic cytokine that plays a major role in the development of hepatic fibrosis (Abe et al, ). Treatment of primary cultures of hepatic cells with TGF‐β1 increased type I procollagen mRNA level 13‐fold (Czaja et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…Also several other nutritional compounds are known for their antifibrotic effect in vivo. Green tea revealed ‐ similar to CE ‐ a reduction of fibrosis in Masson's trichrome staining in liver fibrosis .…”
Section: Discussionmentioning
confidence: 79%
“…68) Thus, green tea appears to have hepatoprotective effects. From a clinical point of view, the application of catechins to therapy for hepatitis C appears to be promising.…”
Section: Hepatoprotective Effectsmentioning
confidence: 99%